حق مشاركة المؤلف في حصيلة كل بيع لمصنّفه - مصطفى, سميرة عبد الله (Sulaimani Journal for Humanities, 2007)
The Author right for participation every sells of his compiler The author may conduct of his financial right utilization compiler by abandoning of it to another one there for this right conveys to another one, and the last became the owner of convention. In this cause he be the supersede in all the rights of author in the period of protection of this right. Here we can say the author abandoning of financial utilization of his compiler by the contract of sell not contract of publish. But it happened some time the author abandoning of his owner right in jeep price or he be victim of exploitation of the publisher because his bad circumstances. Also may the author non Known and the publisher exploitation his need for money or for famous. In all this cause the publisher be bad fied and he cost damage to the author because it may his compiler be an expected succeed and sells it more one or two. And the rustle it cost for publisher a big win but the author cant utilization of his compile .There for the legislation recognition for the author of his right to following his name on his compiler and give him a rate from every sell of his compiler.